SIDEMA (Sistem Informasi Desa Menawan) untuk Peningkatan Pelayanan Masyarakat dalam Upaya Mewujudkan Digital Village di Desa Menawan Kabupaten Grobogan - Fikriah, Fari Katul; Nugaraha, Rozaq Isnaini; Verawati, Liesta (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to implement the Menawan Village Information System (SIDEMA) to facilitate data management and services to the community and the dissemination of village information digitally. The implementation of this program includes an initial survey of technology needs, system implementation, implementation of socialization and training for residents and the Menawan Village apparatus, Grobogan Regency. The results of the community service show that the implementation of SIDEMA is able to increase service efficiency and facilitate residents’ access to public information. SIDEMA is expected to function optimally in supporting the Digital Village vision. The evaluation carried out showed that the community was satisfied with the community service activities that had been carried out. Further development and replication of this system to other villages is a strategic step in realizing technology-based villages in Indonesia.